An Imbalance of Calcium and Vitamin D Increases the Risk of Type 2 Diabetes (Review Article) - AlFatlawi, Mustafa Hamza; Alquraishi, Mohammed. K. S.; Hammood, Samah Amer; Al-Fatlawi, Sabreen Ghanem; Alamer, Noor; Al-Buhamrah, Noor Abdul Ridha (Medical Science Journal for Advance Research, 2026)
Background: The relationship between vitamin D levels as well as calcium consumption together with their impact on type 2 diabetes (T2D) development has become a subject of increasing scientific investigation during the past few years. Researchers have begun studying vitamin D as it extends beyond its established function to maintain bone health into multiple body systems which include its capacity to control glucose metabolism. The connection between these two elements operates through multiple channels which include insulin secretion control by pancreatic beta cells together with changes in peripheral tissue insulin sensitivity and the body’s response to ongoing low-grade systemic inflammation. Multiple observational studies together with various detailed meta-analysis studies have found that higher levels of 25-hydroxyvitamin D in circulation help to decrease the chances of developing T2D. The evidence from randomized controlled trials which serve as the ultimate method to demonstrate causation remains unclear. The clinical trials which tested different vitamin D supplementation doses failed to show a constant protective effect against developing T2D which leaves the hypothesis without confirmation. Researchers still need to identify the 25-hydroxyvitamin D concentration which most effectively controls blood sugar levels and reduces diabetes development. Researchers need to establish these thresholds so they can convert observational research results into practical clinical guidelines.